Public awareness of contagious diseases - Samek, Ilona; Jańczyk, Magdalena; Milanowska, Joanna (Journal of Education, Health and Sport, 2021)
Introduction: Restrictions against the COVID-19 pandemic have resulted in a decrease in other contagious diseases. However, their prevention and treatment are still a topical issue. Purpose: To present the public awareness on infectious diseases taking into account the knowledge of people with medical education. Material and method: The study was conducted by means of the author’s questionnaire. 158 questionnaires were collected and analysed. Results: Men and women of different age took part in the survey. Half of the respondents had medical education. The analysis showed that as many as 89.2% of the respondents were aware of the pathogenic factor of influenza, which is the virus. Only a small percentage of respondents had information regarding the number of influenza infections in Poland (10.8%) and worldwide (21.5%). Medics were aware of this in 10.0% and 28.8% respectively. Influenza was admitted by 81.0% of the respondents, while for other infectious disease (except COVID-19) the result was 75.3%. The respondents indicated as the most common route of transmission of infectious diseases the droplet route (66.5%), while fever was the typical symptom (81.0%). Washing hands turned out to be the most important prophylactic behaviour of respondents (50.6%) and especially of students (93.7%). Conclusions: Awareness of infectious diseases among Poles is not at the highest level. Those with medical education have slightly higher knowledge, but it is necessary to introduce educational programmes and update knowledge.